Ethiopia - In Makeda's Footsteps : Towards a Strategy for Pro-Poor Tourism Development - World Bank (Washington, DC, 2012)
The Government of Ethiopia (GOE) has set in train an initiative to develop the tourism sector in Ethiopia. This study supports this objective through in depth analysis of the supply and demand sides of the sector and by proposing a focused and viable strategy to grow tourist visitation and revenues whilst supporting the GOE poverty reduction goals. The study identified that tourism generated approximately US$ 132 million in in country expenditure revenue from a base of about 150,000 foreign visitors who came to Ethiopia for various purposes such as leisure, business and conferences and to visit friends and relatives. The study established that each of these categories of visitor have different expenditure and length of stay characteristics and based on this suggests a strategy of focusing on the development of leisure tourism, identifying this as the segment with the most potential to deliver growth. A final theme focuses on the need to improve demand for tourism and to work on the image of Ethiopia. Several strategies are suggested including marketing and business development support for Ethiopian tour operators and accommodation owners. A major issue identified is that Ethiopia has little defined product being sold in the market place. It is expected that a strategy that defines product, develops it and improves its delivery will yield improved demand and image results.